Development of Science Process Skills Instrument on Ecology Material: A Validity and Reliability Study - Muhammad Wahyu Setiyadi; Sofyan Syamratulangi; Ni Ketut Rapi; Putu Budi Adnyana; Swandi Swandi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
This research uses the Theory-Based Instrument Development Model. This model develops an instrument based on existing theories to ensure that the instrument has a strong theoretical basis. The steps are determining relevant theories, compiling instrument items based on theoretical concepts, validating content with theoretical experts, and testing the reliability and validity of empirical evidence. To determine the validity of the content, the VCR (content validity ratio) and CVI (content validity index) methods are used, item validity and reliability. The result is the validity of the content, the validity of the items, and the reliability of the developed instruments are important aspects in the development of assessment instruments. The development of science process skills instruments has great significance in the context of education. This instrument helps in measuring students' ability to carry out scientific processes such as observing, classifying, measuring, communicating, inferring, predicting, identifying variables, using number, and using spice/time relation Integrated processes: formulating hypotheses, controlling variables, devining operationally, investigating and experimenting. In this study, the science process skill instrument developed obtained the result of content validity declared very valid (0.91) based on the CVR and CVI tests, and based on the empirical test of the validity of the item and reliability (0.940) , it was stated that 21 items of science process skills were in the valid and reliable category.